The rhetorical coherence of Hooker's Preface to the Lawes. Issue 1 (1st April 2014) - Graves, Daniel
Abstract This study questions the current consensus that chapters eight and nine of the Preface to Hooker's Lawes were added quickly on last-minute advice from George Cranmer for polemical purposes. In contrast, this paper argues for the Preface's rhetorical unity by suggesting Hooker had a firm command of his dispositio [layout], and that the Preface we know is the one intended. The justification is threefold. First: the article claims that on textual grounds Cranmer's 'An Excellent Letter' had little to do with the Preface despite claims to the contrary; rather, that letter influenced Hooker's Dedicatory Epistle to Archbishop Whitgift in Book V of the Lawes . To demonstrate this, we will cite five textual relationships between those two texts. Second: we explain the break between chapters seven and eight of the Preface by seeing chapter eight as a form of the classical digressio . Finally, we highlight the thematic unity of the Preface and illustrate how the eighth and ninth chapters form a rhetorical climax.